2019
DOI: 10.1002/jaba.656
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of an indirect assessment for identifying tasks for functional analysis

Abstract: Although a demand analysis is helpful for identifying potential establishing operations for the functional analysis (FA) demand condition, it may not always be practical due to time constraints. A potential alternative is the Negative Reinforcement Rating Scale (NRRS), an indirect assessment tool that may serve as a time efficient alternative to a demand analysis. The experimenter assessed the reliability and validity of the NRRS for 5 individuals with autism spectrum disorder who exhibited problem behavior. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…Jaxon and Levi's clinicians reported that they had previously conducted functional analyses that indicated problem behavior was maintained by escape from instructions. When interviewing their treatment team, the experimenter administered the Negative Reinforcement Rating Scale (Wiggins & Roscoe, 2019) to determine which instructions to include in the test condition of the functional analysis. Liam and Owen's clinicians reported that they had previously conducted functional analyses that indicated problem behavior was maintained by access to tangible items.…”
Section: Functional Analysismentioning
confidence: 99%
“…Jaxon and Levi's clinicians reported that they had previously conducted functional analyses that indicated problem behavior was maintained by escape from instructions. When interviewing their treatment team, the experimenter administered the Negative Reinforcement Rating Scale (Wiggins & Roscoe, 2019) to determine which instructions to include in the test condition of the functional analysis. Liam and Owen's clinicians reported that they had previously conducted functional analyses that indicated problem behavior was maintained by access to tangible items.…”
Section: Functional Analysismentioning
confidence: 99%
“…Behavior analysts use demand assessments to identify low-aversive demands (i.e., demands associated with less challenging behavior) and high-aversive demands (i.e., demands associated with more challenging behavior). During a demand assessment, researchers typically evaluate the rate of challenging behavior (e.g., Roscoe et al, 2009;Wiggins & Roscoe, 2020), the latency to engage in challenging behavior (e.g., Call et al, 2009Call et al, , 2016Schmidt et al, 2014;Zarcone et al, 1999), or demand selection (e.g., Zangrillo et al, 2020) to identify highaversive and low-aversive demands. Behavior analysts may conduct demand assessments for participants with escape-maintained challenging behavior prior to functional analyses (FAs) to identify relevant demands to include during the escape condition (Lloveras et al, 2020).…”
mentioning
confidence: 99%
“…Behavior analysts may conduct demand assessments for participants with escape-maintained challenging behavior prior to functional analyses (FAs) to identify relevant demands to include during the escape condition (Lloveras et al, 2020). The results from these studies indicate that behavior analysts are more likely to identify negatively reinforced challenging behavior when demands that are associated with higher rates of challenging behavior are included in the escape condition (Call et al, 2009(Call et al, , 2016Roscoe et al, 2009;Schmidt et al, 2014;Wiggins & Roscoe, 2020;Zangrillo et al, 2020).…”
mentioning
confidence: 99%